Control and Information Systems for the National Ignition Facility. (1st February 2016) - Brunton, G.; Casey, A.; Christensen, M.; Demaret, R.; Fedorov, M.; Flegel, M.; Folta, P.; Frazier, T.; Hutton, M.; Kegelmeyer, L.; Lagin, L.; Ludwigsen, P.; et al.
Abstract: Orchestration of every National Ignition Facility (NIF) shot cycle is managed by the Integrated Computer Control System (ICCS), which uses a scalable software architecture running code on more than 1950 front-end processors, embedded controllers, and supervisory servers. The ICCS operates laser and industrial control hardware containing 66 000 control and monitor points to ensure that all of NIF's laser beams arrive at the target within 30 ps of each other and are aligned to a pointing accuracy of less than 50 μm root-mean-square, while ensuring that a host of diagnostic instruments record data in a few billionths of a second. NIF's automated control subsystems are built from a common object-oriented software framework that distributes the software across the computer network and achieves interoperation between different software languages and target architectures. A large suite of business and scientific software tools supports experimental planning, experimental setup, facility configuration, and post-shot analysis. Standard business services using open-source software, commercial workflow tools, and database and messaging technologies have been developed. An information technology infrastructure consisting of servers, network devices, and storage provides the foundation for these systems. This paper is an overview of the control and information systems used to support a wide variety of experiments during the National Ignition Campaign.